2013
DOI: 10.1049/iet-com.2012.0594
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis for multiple‐input multiple‐output‐maximum ratio transmission systems with channel estimation error, feedback delay and co‐channel interference

Abstract: In this study, the authors analyse the impact of channel estimation error (CEE), feedback delay (FD), and co-channel interference (CCI) on the performance of multiple-input multiple-output (MIMO) systems deploying maximum ratio transmission (MRT). In particular, the authors derive closed-form expressions for the ergodic capacity and the symbol error rate (SER) as well as the outage probability (OP). In addition, to reveal the effect of CEE, FD and CCI on the MIMO-MRT system, the authors adopt more simplified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Compared with (2), it can be found that the error term due to the imperfect CSI is added in the output signal. Since the error term can be demodulated with envelope detection [20], it should be treated as signal as in [17] rather than the noise or interference as in [14]- [16]. As a result, after the necessary computations, the output SNR at the receiver can be expressed as…”
Section: System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with (2), it can be found that the error term due to the imperfect CSI is added in the output signal. Since the error term can be demodulated with envelope detection [20], it should be treated as signal as in [17] rather than the noise or interference as in [14]- [16]. As a result, after the necessary computations, the output SNR at the receiver can be expressed as…”
Section: System Modelmentioning
confidence: 99%
“…In [15], the authors have studied the performance of MIMO wireless communications with transmit BF and receive MRC in the presence of channel estimation error and co-channel interferences. Furthermore, the joint impacts of channel estimation error, feedback delay and co-channel interference on the performance of MIMO systems employing MRT has been examined in [16]. It is worth-mentioning that the error term due to imperfect CSI is treated as noise or interference in [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIMO systems that employ both the MRT and the receive antenna selection are studied in the study of Coskun and Kucur by using Nakagami‐ m distribution. In the study of Chu, Duong, and Zepernick, the authors analyze the delay in feedback and co‐channel interference and the impact of the channel estimation error on the performance of MIMO systems employing MRT. In the study of Parfait, Kuang, and Jerry, the performance of zero‐forcing in MRT system is analyzed and compared in a downlink massive MIMO system.…”
Section: Introductionmentioning
confidence: 99%